2015
DOI: 10.1080/21551197.2015.1022681
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Home-Delivered Meal Program on Nutritional Risk, Dietary Intake, Food Security, Loneliness, and Social Well-Being

Abstract: Maintaining independence and continuing to live at home is one solution to manage the rising health care costs of aging populations in the United States; furthermore, seniors are at risk of malnutrition and food insecurity. Home-delivered meal programs are a tool to address food, nutrition, and well-being concerns of this population. Few studies have identified outcomes from these programs; this pilot study reviews the nutritional status, dietary intake, well-being, loneliness, and food security levels of seni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 12 publications
3
69
0
1
Order By: Relevance
“…[57] A home delivered meals program for elderly participants was effective in reducing food insecurity and improving nutritional status. [58]…”
Section: Nutrition Support Interventionsmentioning
confidence: 99%
“…[57] A home delivered meals program for elderly participants was effective in reducing food insecurity and improving nutritional status. [58]…”
Section: Nutrition Support Interventionsmentioning
confidence: 99%
“…Nine studies involved a pre- post-assessment of home-delivered meals on some outcome (57, 58,59, 60, 61, 62, 63, 64, 65). These studies attempted to determine: 1) whether receipt of home-delivered meals improved participants’ status along some dimension (e.g., nutritional status, nutrition risk) (57, 58,59, 60, 61, 62); 2) whether changes were observed in participants’ use of formal or informal care (64); or 3) what accounted for withdrawal or continuance in home-delivered meals programs (63, 65).…”
Section: Resultsmentioning
confidence: 99%
“…These studies attempted to determine: 1) whether receipt of home-delivered meals improved participants’ status along some dimension (e.g., nutritional status, nutrition risk) (57, 58,59, 60, 61, 62); 2) whether changes were observed in participants’ use of formal or informal care (64); or 3) what accounted for withdrawal or continuance in home-delivered meals programs (63, 65). More recent studies included outcome measures of anxiety, well-being, and loneliness in addition to the standard nutritional status outcomes (57, 58). All studies examining changes in participants’ status identified improvements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Cho et al [12] discuss findings from Hospital or Emergency Room Patients Served by Meals On Wheels, Inc. and show that patients who received home-delivered meals, among other services, had lower than expected rates of healthcare utilization three and six months after initial receipt of the services. Wight and colleagues [13] report that community-dwelling seniors who qualify to receive home delivered meals have a high prevalence of malnutrition and risk for malnutrition, as well as food insecurity. However, they showed that after receiving home-delivered meals even for a short period of time that significant improvements were observed for nutritional status, dietary intake, food security, loneliness and mental wellbeing.…”
mentioning
confidence: 99%